Women Lifers: What the United States Sentencing Commission Data Tell Us about Women Eligible for and Sentenced to Life Without Parole - Spohn, Cassia (Victims & offenders, 2023)
The current study builds on recent research assessing the decision to impose life imprisonment without the possibility of parole (LWOP), focusing on females convicted in US District Courts. Using USSC data from 2010 to 2017 and an intersectional approach, we described the characteristics of life-eligible and life-sentenced women and examined the factors that predict life eligibility among females and males . Black women faced higher odds of life eligibility than White or Hispanic women and life experiences and case processing factors affected life eligibility differently for women and men. These results highlight the importance of intersectionality for understanding gendered sentencing pathways.